2020
DOI: 10.1038/s41598-020-71334-x
|View full text |Cite
|
Sign up to set email alerts
|

Analogue pattern recognition with stochastic switching binary CMOS-integrated memristive devices

Abstract: Biological neural networks outperform current computer technology in terms of power consumption and computing speed while performing associative tasks, such as pattern recognition. The analogue and massive parallel in-memory computing in biology differs strongly from conventional transistor electronics that rely on the von Neumann architecture. Therefore, novel bio-inspired computing architectures have been attracting a lot of attention in the field of neuromorphic computing. Here, memristive devices, which se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 69 publications
(80 reference statements)
0
26
0
Order By: Relevance
“…Stochastic operation of binary synapses is one possible solution 28 . Suri, et al showed that the probabilistic SET and RESET of binary memristors can be used for STDP-based learning 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Stochastic operation of binary synapses is one possible solution 28 . Suri, et al showed that the probabilistic SET and RESET of binary memristors can be used for STDP-based learning 19 .…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure S10, Supporting Information, crossbar arrays of the organic memristor were used for a synapse layer. Based on the result in Figure 5e, we assumed the organic memristor was operated as a binary memory cell [43] with a broad read window for the perfect separation of resistance states in sensing operation, and three cells were formed for an artificial synapse with 3 bits of memory. In addition, the ideal vector-matrix multiplication operations which are importantly used in inference were assumed in the organic memristor crossbar array.…”
Section: Resultsmentioning
confidence: 99%
“…From the literature, two main pathways are identified, these are the single-device and the compound-device architectures. On the side of single device architectures, extensive studies exist on the variability phenomenon both for d2d and c2c aspects ( Jo et al, 2009 ; Suri et al, 2013 ; Yu et al, 2013a ; Naous et al, 2016 ; Wenger et al, 2019 ; Zahari et al, 2020 ). The idea to incorporate multiple resistive devices into a synapse has been introduced earlier ( Gaba et al, 2013 ; Bill and Legenstein, 2014 ; Hu et al, 2014 ; Singha et al, 2014 ; Boybat et al, 2018 , 2019 ; Payvand et al, 2018 , 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Common for previous works published on the subject of stochastic switching of ReRAM devices in neural networks is the utilization of behavioral models. These lead to voltage-dependent switching probability models such as the Poisson distribution ( Jo et al, 2009 ; Gaba et al, 2013 ; Naous et al, 2016 ; Payvand et al, 2018 ; Zahari et al, 2020 ), sigmoidal distribution ( Wenger et al, 2019 ), Gaussian distribution ( Yu et al, 2013b ) and lognormal distribution ( Medeiros-Ribeiro et al, 2011 ; Hu et al, 2014 ), and even linear dependence ( Singha et al, 2014 ). By definition, these models only capture the minimal required behavioral aspects and possess little to no predictive character for any setup modification.…”
Section: Introductionmentioning
confidence: 99%